The TPACK-in-Practice Workshop Approach: A Shift From Learning the Tool to Learning About Technology-Enhanced Teaching - Jamani, Kamini Jaipal; Figg, Candace (Proceedings of the International Conference on e-Learning (Online), 2013)
Technology professional development workshops primarily focus on technical skill training and these skills are often taught out of context and seem remote from classroom practice. How can educators learn how to teach with technology in a variety of disciplinary areas so that their professional learning experiences are considered valuable and are readily integrated into their teaching practice? This paper presents the Framework of TPACK-in-Practice.concrete teacher actions, or practice-derived teacher knowledge about teaching content with technology-and illustrates the framework's usefulness in developing the TPACK-in-Practice Workshop approach to design content-centric technology professional development experiences for teachers and higher education faculty. A content-centric approach to teaching with technology advances the learning of content goals through the use of technology, and a current framework that has been adopted by teacher educators internationally is that of TPACK, proposed by Mishra & Koehler. This model, developed from Shulman's notion of pedagogical content knowledge, illustrates the interactions among technology knowledge (TK), pedagogical knowledge (PK), and content knowledge (CK) in teaching. To bridge the gap between the theoretically defined knowledge components of the TPACK model, and the actions that demonstrate these knowledge components in practice, the authors conducted qualitative, longitudinal studies with pre-service teachers and in-service teachers in the field. Findings of these studies led to the development of the Framework of TPACK-in-Practice which identifies teacher actions that characterize teacher knowledge important for successful tech-enhanced teaching, specifically the knowledge components of TCK-in-practice, TPK-in-practice, and TPCK-in-practice. Subsequent implementation of the Framework of TPACK-in-Practice in pre-service technology courses and with in-service teachers revealed four design elements promoting a shiftfrom learning the tool to learning how to teach with the tool (technology-enhanced teaching). These elements include: (a) modeling a technology-enhanced activity (learning with the tool) to set the context and purpose for tool use, (b) integrating 'pedagogical dialogue' in a modeled lesson, (c) developing activity-specific technical skills (TK in context) through short tool demonstrations, and (d) applying TPACK-in-Practice to design an independent task. The preceding four elements constitute the TPACK-in-Practice Workshop approach and provide guidelines for designing content-centric professional development workshops to develop teacher knowledge about how to teach with technology. The TPACK-in-Practice Workshop approach enables teachers to leave professional development workshops with the knowledge to be able to teach WITH the technology rather than just the skills be use the technology as is promoted in traditional technology training workshops. [PUBLICATION ABSTRACT]